Ethephon As a Potential Abscission Agent for Table Grapes: Effects on Pre-Harvest Abscission, Fruit Quality, and Residue - Ferrara, Giuseppe; Mazzeo, Andrea; Matarrese, Angela M. S.; Pacucci, Carmela; Trani, Antonio; Fidelibus, Matthew W.; Gambacorta, Giuseppe (Frontiers in Plant Science, 2016)
Some plant growth regulators, including ethephon, can stimulate abscission of mature grape berries. The stimulation of grape berry abscission reduces fruit detachment force (FDF) and promotes the development of a dry stem scar, both of which could facilitate the production of high quality stemless fresh-cut table grapes. The objective of this research was to determine how two potential abscission treatments, 1445 and 2890 mg/L ethephon, affected FDF, pre-harvest abscission, fruit quality, and ethephon residue of Thompson Seedless and Crimson Seedless grapes. Both ethephon treatments strongly induced abscission of Thompson Seedless berries causing >90% pre-harvest abscission. Lower ethephon rates, a shorter post-harvest interval, or berry retention systems such as nets, would be needed to prevent excessive pre-harvest losses. The treatments also slightly affected Thompson Seedless berry skin color, with treated fruit being darker, less uniform in color and with a more yellow hue than non-treated fruit. Ethephon residues on Thompson Seedless grapes treated with the lower concentration of ethephon were below legal limits at harvest. Ethephon treatments also promoted abscission of Crimson Seedless berries, but dropper-harvest abscission was much lower (49%) in Crimson Seedless compared to Thompson Seedless. Treated fruit were slightly darker than non-treated fruit, but ethephon did not affect SSC, acidity, or firmness of Crimson Seedless, and ethephon residues were below legal limits.